Water-energy nexus: Impact on electrical energy conversion and mitigation by smart water resources management. (15th September 2017) - Gjorgiev, Blaže; Sansavini, Giovanni
Highlights: The issues to energy conversion stemming from the water-energy nexus are investigated. The objective is to minimize power curtailments caused by critical river water conditions. A water-energy nexus model for smart management of water resources is developed. Systemic risks to energy conversion stem from critical temperature and flow regimes. Full coordination of the hydrologically-linked units provides the most effective strategy. Abstract: The water-energy nexus refers to the water used to generate electricity and to the electric energy used to collect, clean, move, store, and dispose of water. Water is used in all stages of electric energy conversion making power systems vulnerable to water scarcity and warming. In particular, a water flow decrease and temperature increase in rivers can significantly limit the generation of electricity. This paper investigates the issues to energy conversion stemming from the water-energy nexus and mitigates them by developing a model for the smart utilization of water resources. The objective is to minimize power curtailments caused by a river water flow decrease and a temperature increase. The developed water-energy nexus model integrates the operational characteristics of hydro power plants, the environmental conditions, the river water temperature prediction and thermal load release in river bodies. The application to a hydraulic cascade of hydro and a thermal power plants under drought conditions shows that smart water management entails a significant reduction of power curtailments. In general, the full coordination of the power outputs of the units affected by the hydrological link provides the most effective mitigations of the potential issues stemming from the water-energy nexus. Finally, critical temperature and flow regimes are identified which severely impact the energy conversion and may cause systemic risks in case the generators in one region must be simultaneously curtailed.